Measuring the efficacy of positioning aids for capturing 3D data in different clothing configurations and postures with a high-resolution whole-body scanner. (February 2021) - Schwarz-Müller, Frank; Marshall, Russell; Summerskill, Steve; Poredda, Christoph
Highlights: Positioning aids were developed for the use in a high-resolution 3D scanner. A study assessed the efficacy of the positioning aids in reducing human variability. The mean absolute variability ( MAV ) was introduced as measure of efficacy. The variability was reduced to <10 mm in both the standing and seated posture. They allow the precise superimposition of scans without compromising data integrity. Abstract: Numerous surveys have been conducted worldwide to capture 3D anthropometric data of individuals scanned in tight underwear. However, such semi-nude data are inadequate for designing workspaces for specialised user populations who wear protective clothing and equipment. Determining the offset between semi-nude and clothed configurations requires the same individual to be repeatedly scanned in exactly the same posture. Specifically, for the use in a high-resolution 3D body scanner, positioning aids for the standing and seated posture were developed to stabilise the posture during the scanning process without compromising data integrity. The mean absolute variability ( MAV ) index was introduced to determine the efficacy of the positioning aids. It was shown that the positioning aids efficiently reduce the variability in fore-and-aft and side-to-side directions. This way the precondition was created for the precise superimposition of scans permitting the offset between diverse clothing configurations to be determined.